La Midinette, la cage et l’oiseau - Anne Monjaret (Images Re-Vues)
The "midinette", a Parisian fashion worker, heir to the "grisette" who inspired writers, painters, engravers and sculptors, gave rise at the turn of the nineteenth and twentieth centuries to numerous representations featuring her, alone or accompanied. These representations then remain in place for a long time. And among the symbolic attributes of particular interest to us here is the bird (or birds) and the cage. How can such an association be explained? What does this language of birds refer to? What does it tell us about this female figure? A canary in a cage, a pretty couple or a flock of sparrows - these scenes seem to paint a metaphorical picture of the moments in the life of this figure, in love and working, between a gendered and social confinement from which she is trying to free herself, and the freedom to emancipate herself and access another world. Are these images not the expression of a bourgeois and masculine morality, conveying norms of convenience?